PROCEDURA KONKURSOWEGO DOBORU KADR KIEROWNICZYCh. PROBLEMATYKA PRAWNA - Duraj, Tomasz (Zeszyty Prawnicze, 2016)
THE COMPETITIVE SELECTION PROCEDURE FOR MANAGEMENT STAFF: LEGAL ISSUES Summary This analysis relates to the legal issues in the competitive selection of management staff. Under the current provisions in Poland many legal acts pertain to this issue, giving an inhomogeneous set of regulations for the principles of conducting such procedures in particular domains of public, social and economic affairs. The subject of this article is a detailed description of the stages of the procedure for the competitive selection of management staff. Good legislation to regulate the selection procedures for competitions for management appointments will have a significant influence on the effectiveness of the adopted method of selection. The author presents the successive stages of the procedures for such competitions and conducts an in-depth legal analysis, paying specific attention to legal doubts arising in connection with the application of the current law. On the basis of his analysis he formulates some proposals de lege ferenda addressed to the legislator on the introduction of requisite amendments and supplements to the legal regulations for the procedure of competitive selection of management staff.